In silico pharmacokinetic and toxicological evaluation of Cephalonium antibiotic in human and environmental health - Fonseca, Evelyn Gabriely Martins; Motta, Luiz Frederico (Seven Editora, 2023)
Antibiotics are drugs that have revolutionized the world scenario for the treatment of infectious diseases caused by bacteria and have reduced morbidity and mortality rates worldwide. Due to the increase in population and veterinary treatment, the use of medicines for health and treatment in animals has increased considerably. In this context, the present study aimed to evaluate the potential pharmacokinetic and toxicological impacts of the veterinary antibiotic Cephalonium on human and environmental health. In this work, predictions of molecular properties for the antibiotic were performed with the aid of in silico methodologies. In silico pharmacokinetic studies have shown promising results, as the antibiotic has a low rate of human intestinal absorption, is not permeable by the blood-brain barrier, and does not inhibit hepatic isoenzymes. The antibiotic showed promising data about the Ames test, showing itself to be non-toxic (non-mutagenic), not carcinogenic, with acute oral toxicity classified as category III (low human toxicity). In the in silico evaluations of environmental toxicity, Cephalonium was not toxic for bees and crustaceans, however, it showed a toxicity for fish. Therefore, it is noteworthy that Cephalonium promotes environmental and consequently human contamination by the presence of antibiotic residues present in food. DOI:https://doi.org/10.56238/alookdevelopv1-001